2021
DOI: 10.3390/f12101403
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Macrobenthic Abundance and Community Composition to Mangrove Vegetation

Abstract: The mass planting of mangroves has been proposed as a mitigation strategy to compensate for mangrove loss. However, the effects of mangrove vegetation on the abundance and community composition of macrobenthos remain controversial. The macrobenthic communities in four intact mangrove forests with different conditions and the adjacent nonvegetated mudflats of two mangrove species with distinct stand structures on the western coast of Taiwan were examined. Some macrobenthic taxa occurred only in the mangroves, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Also, nMDS showed that species composition differed between habitats. We observed similar results to those of Checon et al (2017) [29], Leung (2015) [31], and Pan et al [5]. Many studies, including the present study, show that the presence of vegetation and structural components (such as roots, algal mats, and pneumatophores) significantly changed sediment characteristics.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Also, nMDS showed that species composition differed between habitats. We observed similar results to those of Checon et al (2017) [29], Leung (2015) [31], and Pan et al [5]. Many studies, including the present study, show that the presence of vegetation and structural components (such as roots, algal mats, and pneumatophores) significantly changed sediment characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…In the mangrove ecosystem, prop roots and pneumatophores helped trap detritus and litter, and also weakened wave action to increase sedimentation rates, which resulted in finer sediment and more organic matter [31,54]. The abundance and diversity indices decrease with the increase in root biomass, which may lead to inhibition and reduction in the burrowing behavior and feeding activity [5,31,55]. As reported by Leung (2015) [31] and Checon et al (2017) [29], the density of polychaetes in the mangrove was lower than those in mudflats, and the density of polychaetes was negatively correlated with root biomass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation